ACCURACY TEST OF BRUNTON COMPASS AND SUUNTO COMPASS IN MEASURING QIBLA DIRECTION - Muhammad Hidayat; Arwin Juli Rakhmadi; Abdul Rahman Cemda; Marataon Ritonga (Proceeding International Seminar of Islamic Studies, 2023)
One of the methods in measuring Qibla Direction is using a compass. The compass itself consists of various types and has different levels of accuracy. Therefore this trial was conducted to determine the level of accuracy between the Brunton compass and the Suunto compass in measuring Qibla direction. This research method uses the field research method or field research using the Brunton Compass, Suunto Compass, Theodolite, Arc Roller, Solar Azimuth Data, Magnetic Deviation Data for Medan City and other supporting data/instruments. The results of this study indicate that the Brunton compass has higher accuracy than the Suunto compass which was tested using a theodolite.